2017
DOI: 10.1017/s0022149x17001146
|View full text |Cite
|
Sign up to set email alerts
|

Description of Metagonimus pusillus sp. nov. (Trematoda: Heterophyidae): phylogenetic relationships within the genus

Abstract: As a result of experimental studies conducted in the Russian southern Far East, adult worms from the genus Metagonimus were obtained. A comparative analysis of the morphometry of these worms with other Metagonimus representatives showed that they are most similar to M. katsuradai Izumi, 1935 and M. otsurui Shimazu & Urabe, 2002 found in Japan, due to the ratio of suckers and the positions of the testicle, uterus and vitellaria. However, Russian worms differ from species in Japan by other metric characters: the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…n. (7.1–7.4%), which is located at a basal position of the tree. These values are comparable to interspecies genetic distances between representatives of related families, namely Opisthorchiidae Looss, 1899 and Heterophyidae Leiper, 1909 (Tatonova et al ., 2018; Besprozvannykh et al ., 2019). Fixed amino acid substitutions have also been identified between analysed species (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…n. (7.1–7.4%), which is located at a basal position of the tree. These values are comparable to interspecies genetic distances between representatives of related families, namely Opisthorchiidae Looss, 1899 and Heterophyidae Leiper, 1909 (Tatonova et al ., 2018; Besprozvannykh et al ., 2019). Fixed amino acid substitutions have also been identified between analysed species (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Fluke members in the genus Metagonimus Katsurada, 1912 (Digenea: Heterophyidae) included more than 7 nominal species; i.e., M. yokogawai Katsurada, 1912, M. takahashii Suzuki, 1930, M. minutus Katsuta, 1932, M. katsuradai Izumi, 1935, M. otsurui Saito and Shimizu, 1968, M. miyatai Saito et al, 1997, and M. hakubensis Shimazu, 1999 [ 10 , 11 ]. Recently, 2 species, M. suifunensis Shumenko et al, 2017 and M. pusillus Tatonova et al, 2018, were additionally reported in Russia [ 12 , 13 ]. Among these 9 Metagonimus species, 3 ones, i.e., M. yokogawai , M. takahashii , and M. miyatai , are distributed in this country.…”
Section: Background and Purposementioning
confidence: 99%
“…This species was described by Katsurada (1912) in Japan as Heterophyes yokogawai and then reported from other Asian countries (South Korea, Taiwan, and India), as well as Russia, Israel and several European countries (Bulgaria, Czech Republic, Hungary, Serbia, and Spain) (Yu and Mott 1994 ; Rácz and Zemankovics 2002 ; Chai et al 2009 ; Pornruseetairatn et al 2016 ). However, the global distribution of M. yokogawai has yet to be confirmed, as other species of Metagonimus have a limited geographical distribution, with most species described from East Asia (Shimazu 1999 , 2002 ; Chai and Lee 2002 ; Shimazu and Urabe 2002 ; Kino et al 2006 ; Shumenko et al 2017 ; Tatonova et al 2018 ; Nakao et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%